Paraklesis to the Great Martyr John the New of Suceava according to the Moldavian Manuscript of 1655 with Variant Readings from an East Slavic Manuscript of the Late Seventeenth Century (prepared by Sergei Temchin) - Temchin, Sergei (Senoji Lietuvos literatūra, 2024)
-